Experimental study of carbon dioxide hydrate formation in the presence of graphene oxide. (15th November 2020) - Liu, Ni; Chen, Litao; Liu, Caixia; Yang, Liang; Liu, Daoping
Abstract: The application of gas hydrate technology is limited by the slow formation rate and low gas storage capacity of gas hydrates. In this study, the effects of graphene oxide (GO) and mixed additives consisting of GO, sodium dodecyl sulfate (SDS), and tetrahydrofuran (THF) on CO2 hydrate formation were studied experimentally under quiescent conditions. The addition of 0.0025 wt% GO effectively shortened the induction time of CO2 hydrate formation by 74% compared with that in pure water; this promotion effect decreased with increasing GO concentration. However, the gas consumption and gas storage capacity of the hydrate formed under these conditions using GO alone were small. The effects of mixed additives consisting of various concentrations of GO, 0.3% SDS, and 4% THF on the CO2 hydrate formation were further studied to overcome this disadvantage. Secondary hydrate nucleation occurred in systems containing the SDS/THF/GO mixed additives, which greatly increased the gas storage capacity of the hydrate. The largest gas storage capacity enhancement (152%) was achieved in the mixed additive system containing 0.0025 wt% GO. The mechanisms by which the different additives promote hydrate formation have also been analyzed. Highlights: The induction time was reduced by 74% in GO-only system than that in pure water. Secondary hydrate nucleation occurred in SDS/THF/GO system. The addition of GO reduced the hydrate formation time by 59% compared to SDS/THF. The gas storage capacity in mixed system was 6.1 times that in GO-only system.